More than 50% of hip replacements seem to last 25 years. (31st December 2019) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: How long does a hip replacement last? A systematic review and meta-analysis of case series and national registry reports with more than 15 years of follow-up Evans JT, Evans JP, Walker R, Blom AW, Whitehouse MR, Sayers A Published on 16 February 2019 Lancet 2019;393:647-54 This study was supported by the NIHR Biomedical Research Centre at the University Hospitals Bristol NHS Foundation Trust and the University of Bristol. To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000781/more-than-50-of-hip-replacements-appear-to-last-25-years